2022
DOI: 10.7566/jpsj.91.093701
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Skyrmion Crystal Phase in Centrosymmetric Distorted Triangular-Lattice Antiferromagnets

Abstract: The stability of a magnetic skyrmion crystal in a centrosymmetric orthorhombic lattice system is numerically investigated. By performing the simulated annealing for an effective spin model with the momentumresolved interaction on a uniaxially distorted triangular lattice, we find that the skyrmion crystal is robustly realized when dominant interaction channels consist of the double-Q structure in momentum space. Moreover, we show that an anti-type skyrmion crystal with the opposite skyrmion number is obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…The formation of the R-SkX with the triple-Q modulation is reasonable, since the contribution to the free energy in the coupling form of (S 0 • S Q 1 )(S −Q 3 • S Q 4 ) occurs like the triangular SkX in hexagonal systems owing to the relation of the triple-Q ordering vectors as Q 1 + (−Q 3 ) + Q 4 = 0. Indeed, it was shown that a similar R-SkX remains stable on a uniaxially-distorted triangular lattice [47]. The above tendency holds for J Q 2 /J Q 1 > 1.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The formation of the R-SkX with the triple-Q modulation is reasonable, since the contribution to the free energy in the coupling form of (S 0 • S Q 1 )(S −Q 3 • S Q 4 ) occurs like the triangular SkX in hexagonal systems owing to the relation of the triple-Q ordering vectors as Q 1 + (−Q 3 ) + Q 4 = 0. Indeed, it was shown that a similar R-SkX remains stable on a uniaxially-distorted triangular lattice [47]. The above tendency holds for J Q 2 /J Q 1 > 1.…”
Section: Resultsmentioning
confidence: 88%
“…In these situations, the SkX is invariant under threefold or fourfold rotation. Meanwhile, it was revealed that SkXs remain stable in the low-symmetric lattice structures [42][43][44][45][46][47] and nonsymmorphic lattice structures with the screw axis [48]. In addition, a recent experiment has shown that a rhombic SkX was observed in the centrosymmetric tetragonal magnet EuAl 4 [49][50][51][52][53], where the importance of a spin-lattice coupling through a tetragonal-to-orthorhombic structural distortion was indicated in realizing such a low-symmetric SkX [54,55].…”
Section: Introductionmentioning
confidence: 99%